Effect of allicin and its mechanism of action in purine removal in turbot. Issue 10 (27th August 2020) - Li, Tingting; Ren, Likun; Wang, Dangfeng; Song, Minjie; Li, Qiuying; Li, Jianrong
Abstract: Low‐purine food is not only the focus of gout patients, but also the focus of contemporary green diet development. Fish are usually considered as high‐purine foodstuff because of the high nutritional value and high purine content. Therefore, it is necessary to reduce purine content in fish to ensure that they are suitable for patients with hyperuricemia or gout. In this study, the effect of allicin on purine reduction in turbot during cooking was investigated using high‐performance liquid chromatography, and the change of xanthine oxidase (XO) activity was also studied. Molecular docking analysis was further performed to elucidate the mechanism of purine reduction by allicin. The results revealed that in the step of soaking, allicin could reduce purine content in fish by slightly enhancing XO activity, promoting hypoxanthine transformation into xanthine. The removal of total purines in experimental and control group reached 70.45% and 57.20%, respectively. Moreover, allicin could change the thermal stability of xanthine by providing an acidic environment, resulting in the rapid decrease of xanthine and hypoxanthine levels by boiling. Thus, this study provides a simple method to decrease purine levels, suggesting a possibility that allicin can function as a purine remover in food.